Novel self-renewal hash chain scheme based on (t,n) threshold and division tree - Hai-ping HUANG; Ting DAI; Ru-chuan WANG; Xiao-lin QIN; Jiu-tian CHEN (Tongxin xuebao)
The introduction of renewal hash chain overcame resource-constrained defect in traditional hash chains,but the existing renewable schemes had still held unsatisfactory performance especially on security and complexity.The definitions of repetition,division and division-tree was proposed,and then a novel self-renewable hash chain construction scheme was put forward based on division and (,t n)-Mignotte's threshold Chinese remainder theorem secret sharing scheme.From three aspects of key space,twice authent ion and provable security,it theoretically proves that the proposed hash scheme could ensure the novel seed value regenerated safely and resisting the middle-man attack effectively.Simulation experiments demonstrate that the novel scheme obtains equal or more satisfactory performances on the costs of communication,computation and storage than typical schemes.